ANALYSIS OF FRONTLINE DEMONSTRATION CONDUCTED ON SOIL TEST BASED FERTILIZER APPLICATION IN RICE - P. SUJATHAMMA AND S. BALAJI NAYAK (The Bioscan, 2018)
Frontline demonstration on soil test based fertilizer application in rice was conducted during kharif season from 2014 to 2016 in farmers’ fields of Kurnool district of Andhra Pradesh to assess the impact of soil test based fertilizer application in rice on yield, economics and to analyse the performance of this in farmers’ fields. Study revealed that application of nitrogen, phosphorus and potassium based on soil test values resulted in an average yield increase of 3.5 per cent over the farmers practice. Application of nitrogen, phosphorus and potassium nutrients based on soil test values recorded Rs. 11,306 ha-1 higher average net returns over farmers practice. Soil test based fertilizer application recorded an average B:C ratio of 2.72 against farmers practice of 2.30 and average technology index of 2.17 per cent. The higher grain yield (62.89q. ha-1), net returns (Rs, 80,369 ha-1), B:C ratio (2.72) and lower technology index (2.17 per cent) indicates the feasibility of soil test based nutrient application in the rice crop of the Kurnool district